Glucosylceramide synthase is involved in development of invariant natural killer T cells - Popovic, Zoran V.; Porubský, Štefan (Frontiers in immunology, 2017)
Invariant natural killer T (iNKT) cells represent a unique population of CD1d-restricted T lymphocytes expressing an invariant T cell receptor (TCR) encoded by Vα14-Jα18 and Vα24-Jα18 gene segments in mice and humans, respectively. Recognition of CD1d-loaded endogenous lipid antigen(s) on CD4/CD8-double positive (DP) thymocytes is essential for the development of iNKT cells. The lipid repertoire of DP thymocytes and the identity of the decisive endogenous lipid ligands have not yet been fully elucidated. Glycosphingolipids (GSL) were implicated to serve as endogenous ligands. However, further in vivo investigations were hampered by early embryonal lethality of mice deficient for the key GSL-synthesizing enzyme glucosylceramide (GlcCer) synthase (GCS, EC 2.4.1.80). We have now analyzed the GSL composition of DP thymocytes and shown that GlcCer represented the sole neutral GSL and the acidic fraction was composed of gangliosides. Furthermore, we report on a mouse model that by combination of Vav-promoter-driven iCre and floxed GCS alleles (VavCreGCSf/f) enabled an efficient depletion of GCS-derived GSL very early in the T cell development, reaching a reduction by 99.6% in DP thymocytes. Although the general T cell population remained unaffected by this depletion, iNKT cells were reduced by approximately 50% in thymus, spleen and liver and showed a reduced proliferation and an increased apoptosis rate. The Vβ-chains repertoire and development of iNKT cells remained unaltered. The GSL-depletion neither interfered with expression of CD1d, SLAM and Ly108 molecules nor impeded the antigen presentation on DP thymocytes. These results indicate that GlcCer-derived GSL, in particular GlcCer, contribute to the homeostatic development of iNKT cells.
Gesehen am 06.06.2018